A natureza em Bacon e a recepção de sua filosofia nas discussões ambientais - Hora, José Sandro Santos (2014)
The overall objective of this research is to analyze the reception of the philosophy of Bacon in certain theoreticians of environmental sciences. The specific objectives are: to explore the Baconian concept of nature, the concept of progress and the absorption of these concepts in environmental sciences. The work is structured in three chapters. The first deals with the concept of nature. The second is about the idea of progress and the last one presents an analysis on certain appropriations of the Baconian philosophy in Hans Jonas, Andrew Brennan and Mauro Grün. The research is fundamental and bibliographic. Thus, the methodological procedures adopted were reading and textual analysis The relevance of the work consists in two fundamental points: Bring the Baconian thought for nvironmental discussions. ii) Criticizes the hegemonic vision of environmental sciences against modernity. It is in this sense that we store expectations to increase the existing bibliography on Bacon, especially with respect to the relevance of his thought. This research seeks to interdisciplinarity in so far as it interacts not only with the ph ilosophy, but also with the sociology, ethics and environmental education.